Gastrointestinal Tract Perforations - de Oliveira Lima Ferraz, Pedro; Varaschin Zeni, João Otávio; Nasr, Adonis; Lopes Matins Filho, Eduardo; Llanos, Juan Carlos [UNESP]; Lopes Matins, Eduardo; Abreu, Phillipe (Springer Nature, 2025)
Gastrointestinal tract perforation occurs when the contents of the gastrointestinal system leak into the abdominal cavity. This condition is characterized by acute, persistent, and intense abdominal pain, which almost always necessitates immediate surgical intervention. Gastrointestinal perforation is considered a surgical emergency, carrying a significant risk of morbidity and mortality. Early intervention is crucial for improving patient outcomes.